TRANSLATION OF THEMATIC STRUCTURE OF DESCRIPTIVE TEXT FROM INDONESIAN INTO ENGLISH - Prayuda, Meikardo Samuel; Silalahi, Theresia Shintanauli Margaretha; Almanda, Fiber Yun (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2022)
This research was made to analyze the translation of the thematic structure of descriptive text from Indonesian into English. The result of this research was that there were some shifts occurred from the source text into the target text on the descriptive translation made by the students. The result was that the most shifts occur on the clause number 5 with 10 shifts. Secondly was clause number 6 with 6 shifts. Thirdly was clause number 9, 10, 11 with each of them consists of 3 shifts. The students who want to make translation of descriptive text from Indonesian into English to pay attention on their translation especially on the shifts that might be occurred on their translation. The shifts of the translation from the source text into the target text might result the shifts of meaning too.